A cristologia de Aparecida: do Jesus do encontro ao discípulo missionário do Pai - Azevedo, Edson Vitor Silva (2023)
The present work seeks to analyze the christological aspects present in the Aparecida document. Indeed, CELAM's most recent publication is a document focused on pastoral actions of the Church in Latin America and the Caribbean. Indeed, it is axiomatic to understand that Aparecida is a reflection ecclesiological. The work seeks to understand the christological aspects written in Aparecida based on descriptions of the Latin American Church and Caribbean conceived at the Conference. Expanding awareness of the relationship between christology and ecclesiology, the work aimed to deepen the understanding of Jesus Christ from the perception of the reality of Latin America and the Caribbean using bibliographical research, in addition to consulting articles and interviews. It was understood that in Aparecida there is a christology explicit in the affirmation of Jesus of Nazareth as the one, prefigured in several illustrations in the Scriptures and result of theological construction, it is path to the divine and the human, emanation of eternal truth and impulse for the defense of life. Furthermore, the christology of Aparecida indicates that Jesus is one who is present with the community, in the needy and in life prayer, in addition to the assimilation of Christ as a disciple and missionary of the Father, which christians are formed. Finally, the work, with the result obtained, investigated the same christology of Aparecida in the results of the First Ecclesial Assembly of Latin America and the Caribbea